Pengelolaan Pembiayaan Pendidikan Madrasah Ibtidaiyah Swasta di Bandung - Inten Nurmalasari; Zamzam Lukmanul Jamil; Ara Hidayat (Universitas Pesantren Tinggi Darul 'Ulum, 2019)
Madrasah Ibtidaiyah Al-Misbah is a nonprofit educational institution that is under the auspices of the Al-Misbah Social Foundation. Since 2004 Madrasah Ibtidaiyah Al-Misbah has no longer collected school fees from students because they have received school operational assistance funds from the government. Each student get IDR. 800,000.00 from the operational costs that are provided by the government. The purpose of this study is to conduct a further study of the financing of private madrasah education and examine how the headmaster made a strategy in meeting school needs that could not be met by school operational assistance funds. The problems that will be examined in this study are: how to manage education funding in Madrasah Ibtidaiyah Al-Misbah Cipadung, Bandung, which is related to financing planning, fund use, supervision and accountability for education funding. To answer that question, the research was conducted with qualitative research methods, a case study approach. The taken case was funding education at the Madrasah Ibtidaiyah Al-Misbah in Cipadung, Bandung City. Management of financing for Madrasah Ibtidaiyah Al-Misbah education includes planning of budgeting; the use of budgeting; budgeting supervision; and finally the accountability reporting stage.